2014
DOI: 10.1186/2193-9772-3-12
|View full text |Cite
|
Sign up to set email alerts
|

The development of phase-based property data using the CALPHAD method and infrastructure needs

Abstract: Initially, the CALPHAD (Calculation of Phase Diagrams) method was established as a tool for treating thermodynamics and phase equilibria of multicomponent systems. Since then the method has been successfully applied to diffusion mobilities in multicomponent systems, creating the foundation for simulation of diffusion processes in these systems. Recently, the CALPHAD method has been expanded to other phase-based properties, including molar volumes and elastic constants, and has the potential to treat electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 109 publications
(128 reference statements)
0
15
0
Order By: Relevance
“…The properties that are currently implemented by the CALPHAD software and databases are the Gibbs energy, molar volume, diffusion, and precipitation kinetics. However, there are many other physical properties that are phase based, and the approach used by the CALPHAD method is well suited for modeling them [55]. The description of these properties will be most likely tied to the thermodynamic description of the individual phases and for expanding the CALPHAD code to include these properties; the availability of a source code for the calculation of thermodynamics will greatly benefit the efficiency of the new code.…”
Section: Discussionmentioning
confidence: 99%
“…The properties that are currently implemented by the CALPHAD software and databases are the Gibbs energy, molar volume, diffusion, and precipitation kinetics. However, there are many other physical properties that are phase based, and the approach used by the CALPHAD method is well suited for modeling them [55]. The description of these properties will be most likely tied to the thermodynamic description of the individual phases and for expanding the CALPHAD code to include these properties; the availability of a source code for the calculation of thermodynamics will greatly benefit the efficiency of the new code.…”
Section: Discussionmentioning
confidence: 99%
“…For example, to consider the diffusion of elements, their mobilities together with the thermodynamic factor need to be described to provide the diffusion coefficient. In addition, there are also interface energies, interface mobilities, elastic constants and other phase-based properties that may be of interest [24]. …”
Section: Computational Thermodynamicsmentioning
confidence: 99%
“…Gheribi and Chartrand [65] proposed a CALPHAD method to predict the thermal conductivity for dielectric and semiconductor phases. Campbell et al [66] presented an extensive review of the modeling of these and other phase-based properties, and showed that the CALPHAD method can even be applied to interphase properties, such as interfacial energies, surface tension of the liquid phase, nucleation, grain boundary diffusion or thermal migration.…”
Section: Models and Gibbs Energy Minimizationmentioning
confidence: 99%